A Synthesis of (–)‐(R)‐ and (+)‐(S)‐Lavandulol, (+)‐Lavandulyl 2‐Methylbutanoate, and (+)‐Lavandulyl Senecioate through Orthoester Johnson–Claisen Rearrangement. Issue 23 (25th June 2013) - Fernandes, Rodney A.; Chowdhury, Asim K.
Abstract: An efficient synthesis of (–)‐( R )‐ and (+)‐( S )‐lavandulol, (+)‐lavandulyl 2‐methylbutanoate and (+)‐lavandulyl senecioate is presented in this paper. The synthetic strategy features a chiral‐pool approach to an allyl alcohol intermediate, and an orthoester Johnson–Claisen rearrangement as the key step. Abstract : An efficient synthesis of (–)‐( R )‐ and (+)‐( S )‐lavandulol, (+)‐lavandulyl 2‐methylbutanoate and (+)‐lavandulyl senecioate is presented. The synthetic strategy features a chiral‐pool approach to an allyl alcohol intermediate, and an orthoester Johnson–Claisen rearrangement as the key step.